Improving Language Skills Through Smart Board Media Ages 5-6 Years in Kindergarten: Peningkatan Kemampuan Bahasa Melalui Media Papan Pintar Usia 5-6 Tahun di Taman Kanak Kanak - Fransiska, Ainun; Destiana, Evie (Universitas Muhammadiyah Sidoarjo, 2023)
Observations made at TK ABA 25 Wage Sidoarjo on children aged 5-6 years showed that there were still difficulties in the development of language skills with a percentage of 44% of children who had reached the development of language skills. This study aims to improve children's language skills through activities to recognize letters using smart board media. The type of research used in this research is classroom action research (CAR) with the techniques used when collecting data using documentation, observation and interviews. The results of this study indicate that there is an increase in language skills through smart board media, namely 44% in the pre-cycle, 64% in the first cycle and 84% in the second cycle. Based on this, it can be concluded that through the media smart board can improve the language skills of children aged 5-6 years in TK Aisyiyah Busthanul Athfal 25 Wage.